Romanian language in preparing and evaluating students - Constantin-Georgel STOICA (Diversitate si Identitate Culturala in Europa)
Assessing students' skills in the Romanian language graduation exams has become a topic of discussion for a large part of the population. Students, parents, and assessors hear about this topic during the simulations of these exams, during regular or special sessions. Most of the time the difficulty of the exam is not given by the complex assessment of the previously taught contents, but by the ambiguous tasks of the subjects in the exams. We therefore, intend on the one hand, to make a pragmatic analysis of the topics proposed for the national exams and on the other hand, to compare them with the exercises in the alternative textbooks, which should be effective tools in preparing students for the graduation exams. The aim of this study is to identify at least some of the system's errors and to suggest a series of solutions that will help teachers to better prepare their students for the graduation exams (both 8th and 12th graders).